2017
DOI: 10.1002/2017gc007077
|View full text |Cite
|
Sign up to set email alerts
|

Heat flow bounds over the Cascadia margin derived from bottom simulating reflectors and implications for thermal models of subduction

Abstract: Understanding the thermal structure of the Cascadia subduction zone is important for understanding megathrust earthquake processes and seismogenic potential. Currently our understanding of the thermal structure of Cascadia is limited by a lack of high spatial resolution heat flow data and by poor understanding of thermal processes such as hydrothermal fluid circulation in the subducting basement, sediment thickening and dewatering, and frictional heat generation on the plate boundary. Here, using a data set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 96 publications
2
35
1
Order By: Relevance
“…Hutnak et al () argued that there is significant (perhaps 20% regionally) hydrothermal heat transfer through places where basement is exposed. Furthermore, Phrampus et al () show that the heat flux inferred from bottom‐simulating reflectors along their Profile A (close to the profile of Figure ) is consistently lower than would be predicted for a purely conductive lower plate (see also Cozzens & Spinelli, ). The maximum heat flux near the deformation front is about 120 mW/m 2 (Phrampus et al, ).…”
Section: Estimates Of Shear Stresses and Temperatures On Subduction Imentioning
confidence: 68%
See 1 more Smart Citation
“…Hutnak et al () argued that there is significant (perhaps 20% regionally) hydrothermal heat transfer through places where basement is exposed. Furthermore, Phrampus et al () show that the heat flux inferred from bottom‐simulating reflectors along their Profile A (close to the profile of Figure ) is consistently lower than would be predicted for a purely conductive lower plate (see also Cozzens & Spinelli, ). The maximum heat flux near the deformation front is about 120 mW/m 2 (Phrampus et al, ).…”
Section: Estimates Of Shear Stresses and Temperatures On Subduction Imentioning
confidence: 68%
“…Furthermore, Phrampus et al (2017) show that the heat flux inferred from bottom-simulating reflectors along their Profile A (close to the profile of Figure 4) is consistently lower than would be predicted for a purely conductive lower plate (see also Cozzens & Spinelli, 2012). The maximum heat flux near the deformation front is about 120 mW/m 2 (Phrampus et al, 2017). Figure 4c displays the mean misfits to the heat flux values (calculated using equation (16) with unit weights) that are obtained by systematically varying Q 0 between zero and 140 mW/m 2 and finding the best fitting value of ′ corresponding to each value of Q 0 .…”
Section: Cascadiamentioning
confidence: 99%
“…These reflectors appear widely distributed both across‐ and along‐strike of the accretionary wedge, extending from Mendocino in northern California to Vancouver Island. A recent compilation by Phrampus et al () found that there is a significant gap in the distribution of BSRs along‐strike of Cascadia upper margin occurs within the Washington segment, between the latitudes 47°N and 48°N, although many of the MCS profiles examined do not extend to the accretionary toe. This is a region where methane bubble stream emissions are particularly abundant on the upper margin and at the continental shelf edge (Figures and S1 in the supporting information).…”
Section: Models For Emission Site Depthsmentioning
confidence: 96%
“…The simulation with hydrothermal circulation is more consistent with the observations. However, along much of the transect, the scatter in the surface heat-flux observations (e.g., Phrampus et al, 2017) spans the predicted differences in surface heat flux between the two models, thus making it difficult to definitively identify a preferred thermal model for this system based on the surface heat-flux distribution alone.…”
Section: Cascadia: Modeling Alteration Of Subducting Materialsmentioning
confidence: 99%